Electrical Behavior of Lanthanum Aluminate (LAO) and Gadolinium Doped Ceria (GDG) Composite Electrolyte for Electrochemical Devices - Najim, Mohd (Engineering, Technology & Applied Science Research, 2023)
The LAO-GDC solid composite electrolyte has been proposed for use in Solid Oxide Fuel Cells (SOFC). The material conductivity of Solid Carbonate-Ceria (SCC) composite electrolytes is 0.04Scm-1 between 400 and 700°C. For this purpose, mixtures of LaAlO3 (LAO) and gadolinium doped ceria Ce0.8Gd0.2O2 (GDC) were created in weight ratios of 3:1, 2:2, and 1:3. The composite electrolyte material was studied separately to improve conductivity. The phase structure and microstructure were studied using an X-Ray Diffractometer (XRD) and Scanning Electron Microscopy (SEM), and the electrical behavior was investigated using Impedance Spectroscopy (IS). The SEM and Energy Dispersive X-ray spectroscopy (EDX) demonstrated a compact structure with an acceptable atomic percentage of constituent elements and a uniform grain distribution. Experimental investigation showed that this composite electrolyte had a high density of LaAlO3 (LAO)-Ce0.8Gd0.2O2 (GDC) composites and an approximate 97% density of its theoretical. The electrical behavior of LAO-GDC composites had the highest value of 0.1Scm-1 at 700°C, which is more extreme than the individual conductivities of LAO and GDC, according to Electrochemical Impedance Spectroscopy (EIS) techniques. Among the three composite ratios of the system, only the weight ratio of 3:1 had better conductivity. The LaAlO3 (LAO)-Ce0.8Gd0.2O2 (GDC) composite material has a higher activation energy of 1.5eV.